2001
DOI: 10.1104/pp.127.3.963
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Phosphate Starvation Responses by Phosphite in Arabidopsis

Abstract: When inorganic phosphate is limiting, Arabidopsis has the facultative ability to metabolize exogenous nucleic acid substrates, which we utilized previously to identify insensitive phosphate starvation response mutants in a conditional genetic screen. In this study, we examined the effect of the phosphate analog, phosphite (Phi), on molecular and morphological responses to phosphate starvation. Phi significantly inhibited plant growth on phosphate-sufficient (2 mm) and nucleic acid-containing (2 mm phosphorus) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
112
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(116 citation statements)
references
References 5 publications
2
112
0
2
Order By: Relevance
“…With 2 mM Phi, no growth or APase induction occurred following subculture of the B. napus cells into the )Pi medium. This corroborates recent studies documenting the detrimental influence of Phi on )Pi, but not +Pi, vascular plants (including B. napus suspension cells; Carswell et al 1996Carswell et al , 1997Foerster et al 1998;Ticconi et al 2001;Varadarajan et al 2002) andyeast (McDonald et al 2001b). 31 P-NMR spectroscopy has demonstrated substantial intracellular Phi accumulation by )Pi plant and yeast cells cultured in the presence of Phi (Carswell et al 1996;McDonald et al 2001b).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…With 2 mM Phi, no growth or APase induction occurred following subculture of the B. napus cells into the )Pi medium. This corroborates recent studies documenting the detrimental influence of Phi on )Pi, but not +Pi, vascular plants (including B. napus suspension cells; Carswell et al 1996Carswell et al , 1997Foerster et al 1998;Ticconi et al 2001;Varadarajan et al 2002) andyeast (McDonald et al 2001b). 31 P-NMR spectroscopy has demonstrated substantial intracellular Phi accumulation by )Pi plant and yeast cells cultured in the presence of Phi (Carswell et al 1996;McDonald et al 2001b).…”
Section: Discussionsupporting
confidence: 91%
“…Although Phi is non-metabolic, it greatly exacerbates the harmful effects of Pi deficiency by specifically preventing the derepression of plant and yeast genes encoding PSI proteins (i.e., APase, high-affinity plasmalemma Pi transporters, etc. ; Carswell et al 1997;Plaxton 1999;McDonald et al 2001aMcDonald et al , 2001bTicconi et al 2001;Abel et al 2002;Varadarajan et al 2002). Phi's prevention of the otherwise massive enhancement of Pi influx capacity that occurs in )Pi B. napus suspension cells provided a rationale for the approx.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, Adalberto et al (2004) and KhozinGoldberg and Cohen (2006) reported that under P-deficiency, chlorophyll synthesis was severely retarded in Azolla caroliniana and Monodus subterraneus, respectively. However, Ticconi et al (2001) reported that total chlorophyll content did not significantly differ between Arabidopsis seedlings grown on P-deficient or P-sufficient medium. In present experiments, the decrease in Ch a+b in P-deficient plants was mostly related to the decrease in Chl a.…”
Section: Discussionmentioning
confidence: 94%